Encapsulation of Pd(II) into superparamagnetic nanoparticles grafted with EDTA and their catalytic activity towards reduction of nitroarenes and Suzuki–Miyaura coupling1. (3rd February 2015) - Azizi, Kobra; Ghonchepour, Ehsan; Karimi, Meghdad; Heydari, Akbar
<x xml:space="preserve">Abstract</x> A robust, safe and magnetically recoverable palladium catalyst was synthesized by anchoring Pd(II) onto ethylenediaminetetraacetic acid‐coated Fe3O4 (Fe3O4@EDTA) magnetic nanoparticles. The Fe3O4 magnetic nanoparticle‐supported Pd(II)–EDTA complex catalyst thus obtained was characterized using scanning and transmission electron microscopies, thermogravimetric analysis, vibrating sample magnetometry, X‐ray diffraction, and inductively coupled plasma atomic emission and Fourier transform infrared spectroscopies. Fe3O4@EDTA–Pd(II) was screened for the Suzuki reaction and reduction of nitro compounds in water. The Pd content of the catalyst was measured to be 0.28 mmol Pd g−1. In addition, the Fe3O4@EDTA–Pd catalyst can be easily separated and recovered with an external permanent magnet. The anchored solid catalyst can be recycled efficiently and reused five times with only a very slight loss of catalytic activity. Copyright © 2015 John Wiley & Sons, Ltd.